A revised generic classification of vittarioid ferns (Pteridaceae) based on molecular, micromorphological, and geographic data. Issue 4 (30th August 2016) - Schuettpelz, Eric; Chen, Cheng-Wei; Kessler, Michael; Pinson, Jerald B.; Johnson, Gabriel; Davila, Alex; Cochran, Alyssa T.; Huiet, Layne; Pryer, Kathleen M.
Abstract: Vittarioid ferns compose a well‐supported clade of 100–130 species of highly simplified epiphytes in the family Pteridaceae. Generic circumscriptions within the vittarioid clade were among the first in ferns to be evaluated and revised based on molecular phylogenetic data. Initial analyses of rbcL sequences revealed strong geographic structure and demonstrated that the two largest vittarioid genera, as then defined, each had phylogenetically distinct American and Old World components. The results of subsequent studies that included as many as 36 individuals of 33 species, but still relied on a single gene, were generally consistent with the early findings. Here, we build upon the previous datasets, incorporating many more samples (138 individuals representing 72 species) and additional plastid markers ( atpA, chlN, rbcL, rpoA ). Analysis of our larger dataset serves to better characterize known lineages, reveals new lineages, and ultimately uncovers an underlying geographic signal that is even stronger than was previously appreciated. In our revised generic classification, we recognize a total of eleven vittarioid genera. Each genus, including the new genus Antrophyopsis (Benedict) Schuettp., stat. nov., is readily diagnosable based on morphology, with micromorphological characters related to soral paraphyses and spores complementing more obvious features such as venation and the distribution of sporangia. A key to the currently recognized vittarioid genera, brief generic descriptions, and five new species combinations are provided.